Survival and persistence of foodborne pathogens in food residues on packaging materials and reduction of Escherichia coli O157:H7 and Salmonella in beef trimmings - Nunnelly, Matthew Charles, author; Sofos, John N., advisor; Woerner, Dale, committee member; Kendall, Patricia, committee member (Colorado State University. Libraries, 2012)
Foodborne pathogens continue to cause health problems for modern consumers of meat products despite efforts to control bacteria in food. New approaches to controlling pathogens and identifying sources of contamination are needed. Some of the most important foodborne pathogens that affect modern food supplies are Salmonella serotypes and Escherichia coli O157:H7, both associated with uncooked meat, and Listeria monocytogenes, a problematic organism for ready-to-eat foods. The objective of this thesis is to investigate survival of E. coli O157:H7 and L. monocytogenes on food packaging materials soiled with meat-based residues, and compare differences of behavior when exposed to different packaging materials and storage conditions. In addition to these investigations, a study comparing resistance of multi drug-resistant and susceptible Salmonella serotypes and E. coli O157:H7 on beef trimmings treated with decontaminating antimicrobials provides valuable information concerning the efficacy of current chemical interventions against Salmonella serotypes that are at the forefront of public health concerns. To evaluate pathogen survival on contaminated food packaging materials, meat based homogenate (10% w/w) was inoculated with a multi-strain mixture of either L. monocytogenes or E. coli O157:H7 and spot-inoculated on packaging material samples, placed in a new, empty petri dish, and stored in incubators set at either 4 or 25° C for up to 130 days. Samples were analyzed regularly until the end of the study. There were survivors of the pathogens on several soiled packaging material types even at 123 or 130 days of storage (L. monocytogenes or E. coli O157:H7, respectively). When the decontamination of beef trimmings contaminated with multi drug-resistant and susceptible Salmonella was compared with E. coli O157:H7, there were very few statistically significant differences (P < 0.05) between the reduction of Salmonella and the response of E. coli O157:H7 to acidified sodium chlorite (1000ppm), peroxyacetic acid (200ppm), and sodium metasilicate (40000ppm). In addition, there were only minor differences between the reductions of antibiotic susceptible Salmonella and multi drug- resistant strains. Results of these studies will aid in quantifying risks associated with contamination of food packaging materials as well as beef trimmings.
Keywords: antibiotic-resistant; persistence; Escherichia coli O157:H7; Salmonella; Listeria monocytogenes